Counselling supervision in Hong Kong: a qualitative study of the intern experience - Tse, Pui Chi (2014)
Internship and supervision are prerequisites for professional counselling training and are vital for professional efficacy. However, research of these training functions in the Hong Kong counselling professional context has been limited. This study aims to explore student counsellors’ perceptions and experience of the counselling supervision in their training within a university-based counselling programme in Hong Kong. The research focuses on how far the culture and cultural assumptions affect the learning process when facing success, struggles and difficulties, and what constitutes and hinders an effective supervision environment for student counsellors. Ten counselling psychology undergraduates, who had already gone through a large part of the internship and supervision process, were invited to participate in this research. A qualitative methodology, including the implementation of Interpretative Phenomenological Analysis (IPA) and semi-structured interviews, was chosen and participants were asked to describe in detail their perceptions and experiences regarding their counselling internship and supervision. The data were generated through the Verbatim records of interviews and records of observation which included nonverbal behavior and the researcher‘s reflection journals. The interview data were analyzed according to themes and subthemes. Five master themes emerged: Guanxi; Perception; Expectation in relation to the learning environment, Mental processing in the learning and Guanxi strategies. The data were analyzed and reanalyzed. Three considerations, cultural, developmental and contextual, in the internship and supervisory experience are portrayed as implications for stakeholders. The notion of Guanxi and Guanxi strategies appears to be the dominant domain to which greater attention needs to be paid in the process of training, especially in regard to counselling supervision. Designers of academic programmes are encouraged to take into serious consideration the dimension of Guanxi in the training. The idiosyncratic desires of the student counsellors and their expectation in relation to the internship setting and supervision environment as well as the mental processing of student counsellors throughout the learning process are revealed. The results have implications for stakeholders with respect to the knowledge and understanding of the impacts of supervision and internship on professional development in our cultural context.